Pneumococcal disease: emergence of serotypes 19A and 7F following conjugate pneumococcal vaccination in a Mexican hospital - Enrique Chacon-Cruz; Yazbeck Velazco-Mendez; Samuel Navarro-Alvarez; Rosa Maria Rivas-Landeros; Maria Luisa Volker; Graciano Lopez-Espinoza (Journal of Infection in Developing Countries)
Introduction: Mexico  was  the  first  country  to  initiate  massive  vaccination  with   heptavalent  pneumococcal  conjugate  vaccine  (PCV-7)  in  children.  There  is  no  information  regarding  pneumococcal  invasive  disease  (PID)  in  children  before  and  after  implementation  of  PCV-7  in  Mexico  or elsewhere  in  Latin America.